Interactive modelling of buildings in Google Earth and GIS: A 3D tool for Urban Planning (Tunjuk Island, Indonesia) - Muhammad Zainuddin Lubis; Wenang Anurogo; Oktavianto Gustin; Andi .; Aditya Hanafi; Dirgan Timbang; Fajar Rizki; Diaz Ariwinata Saragih; Indah Ira Kartini; Hana Cyintia Panjaitan; Marisa Tri Yanti; Herika Muhamad Taki (Politeknik Negeri Batam, 2017)
3D modelling of buildings in Google Earth in Batam city, Indonesia is very important for knowledge about facility, infrastructure, and others.Three-dimensional (3D) visualisations are an interesting method for representing model outcomes. This research In Tunjuk island with coordinate, at Latitude: 0.984123°, and Longitude: 104.225606°, with technical terms, there are two alternative routes for implementation, and they both share the same starting stage. In (Figure 5) visible visual measurements of the master plan that has been made has a length 141.99 metre and width 54.25 metre with location at Latitude 0.984593° and Longitude 104.228073°. In (Figure 5) visible visual measurements of the master plan that has been made has a length 92.96 metre and width 135.46 metre with location at Latitude 0.984593° and Longitude 104.228073°. This paper presented a rapid visualisation tool for supporting the joint decision making in evaluation of design/renewal proposals in Batam City, Tunjuk Island, Indonesia. 3D building using Google Earth (GE) and combaining Geographic Information System (GIS) system be done officially on a sampling or auditing basis by a professional body or by researchers, or it could be done by volunteers and user groups.